Oral Isotretinoin and Its Uses in Dermatology: A Review - Paichitrojjana A; Paichitrojjana A (Dove Medical Press, 2023)
Anon Paichitrojjana,1 Anand Paichitrojjana2 1School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, Bangkok, Thailand; 2Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Anon Paichitrojjana, School of Anti-Aging and Regenerative Medicine, Mae Fah Luang University, 36/87-88 PS Tower 25Fl, Asoke Road, Sukhumvit 21, Klong Toey Nua, Wattana, Bangkok, 10110, Thailand, Tel +66-81-9343050, Email anonpaic@gmail.comAbstract: In 1982, the Food and Drug Administration (FDA) of the United States of America approved isotretinoin (13-cis-retinoic acid), a retinoid derivative of vitamin A, to treat severe recalcitrant acne vulgaris. Apart from its prescribed use for severe acne, evidence suggests that isotretinoin is commonly used off-label to treat mild-to-moderate acne, inflammatory skin conditions, genodermatoses, skin cancer, and other skin disorders. This is due to its anti-inflammatory, immunomodulatory, and antineoplastic properties. Some "off-label" use is successful, while others are ineffective. Therefore, this information is essential to clinicians for deciding on the appropriate use of isotretinoin. In this article, we aim to review the most updated evidence-based data about the use of oral isotretinoin in dermatology.Keywords: isotretinoin, acne vulgaris, rosacea, skin cancer, dermatology